The Role of Trade Unions in Enhancing the Social Activism of Women in Society - Beshimov Khamidjon Sayidovich (Goodwood Publishing, 2026)
Purpose: This study aims to analyze the role of trade unions in enhancing women’s social activism in Uzbekistan, especially within the context of the “New Uzbekistan” development reforms. The focus is on initiatives that promote women's empowerment, employment, and crime prevention through targeted interventions. Research Methodology: The research employs a qualitative-descriptive method using historical-legal, empirical, and statistical analysis. Data were collected from government decrees, official reports, local surveys, and public hearing outcomes in Bukhara region. Results: The study finds that trade unions significantly contributed to resolving the issues of over 3.5 million women nationwide through employment facilitation, micro-loans, social protection, and entrepreneurship support. In Bukhara alone, over 209,000 women benefited from various union-supported programs. The case of a local woman who transitioned from unemployment to a successful business owner illustrates the transformational impact Conclusion: Trade unions have proven to be a vital institutional force in advancing women’s rights, human dignity, and economic participation. Their public oversight role ensures sustainable empowerment at the grassroots level. Limitations: The study is region-specific (Bukhara) and primarily descriptive, lacking comparative or longitudinal analysis across other regions or countries.. Contributions: This article enriches the discourse on gender, labor rights, and civil society by highlighting trade unions as a platform for systemic social change and localized empowerment of women